Wariacyjna metoda pomiaru ryzyka - Pawela-Wargocka, Luiza (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Extending notations and completing some well known results concerning the theory of measurable space the author presents a new approach to the variation of a give function. Using it one introduces the square variational average proposing it as a risk measure instead of the classical one - the standard deviation. Basic properties, examples and a number of applications to the market analysis will be given. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 112-125